Решение задачи упругого изгиба слоистой консоли нормальной линейно распределенной нагрузкой на продольных гранях - Горик, А.В.; Ковальчук, С.Б. (Прикладная механика, 2020)
Наведено точний розв'язок для задачі пружного плоского згину шаруватого композитного бруса малої ширини під дією нормального навантаження, розподіленого на поздовжніх гранях по лінійному закону. Визначально співвідношення для параметрів напружено-деформованого стану отримано шляхом прямого розв'язання плоскої задачі теорії пружності з врахуванням ортотропії пружних властивостей матеріалів шарів бруса та їх зміни по висоті поперечного перерізу за кусково-постійним законом. Отриманий аналітичний розв'язок дає розподіл напружень і переміщень в точках бруса по всьому пакету шарів і дозволяє виконувати практичні розрахунки на міцність і жорсткість, а також будувати розв'язки різних прикладних задач плоского згину композитних брусів. An exact solution of the problem on elastic plane bending of a layered bar of small width under action of the normal loads distributed on the longitudinal faces according to the linear law is presented. The defining relationships for the strain-stress state parameters are obtained by the direct solution of the plane problem of theory of elasticity taking into account orthotropy of the elastic properties of layer’s materials and their changes in the height of a cross-section according to the piecewise constant law. The analytical solution obtained gives the distribution of stress and displacements at the bar points on the whole package of layers and allows to perform the practical calculations for strength and rigidity as well as to construct the solutions of different application problems on plane bending of composite bars.